Legal Review: YouTube Content as Collateral for Credit in Indonesia - Rian, Frans (Faculty of Law, Universitas Riau, 2024)
The objective of this study is to assess the compliance of utilising YouTube material as collateral for bank loans under Republic of Indonesia Government Regulation Number 24 of 2022, which pertains to the Creative Economy (PP Ekraf). This study also explores the possibility of using content from a YouTube account as a type of fiduciary collateral. This research utilises normative legal research to analyse the laws. The data was analysed quantitatively using library research methodologies. According to this research findings, YouTube videos can be classified as intangible assets due to their inclusion of copyrighted information. Under some circumstances, it can serve as collateral for a loan or line of credit. In this scenario, the guarantee requires the completion of the task, regardless of whether the debtor fulfils their obligations or not. The guarantee may stipulate that its provisions must be fulfilled through either a public auction or a private sale. Credit collateral problems can be handled either through litigation in court or by utilising alternative dispute resolution mechanisms, as specified in Article 40 of PP Ekraf.